Using the Experience of Students in Improving the Quality of Services at Universities - Ludwiczak, Anna (Wykorzystanie doświadczeń studentów w doskonaleniu jakości usług w szkołach wyższych, 2023)
The article fits into the subject of quality management systems in Polish universities. The aim was to identify opportunities to use student experience to improve quality in these organizations. A critical review of the literature on the main trends and research methods and tools that are used to identify experiences in university practice was conducted. The analysis showed that it is possible to identify students’ experiences in relation to various aspects of their functioning at the university, which may translate into a better understanding of their needs and expectations. The choice of methods and tools depends on what areas of the organization will be evaluated and what purposes the study is to serve.
Ludwiczak, A. (2023). Using the Experience of Students in Improving the Quality of Services at Universities. In M. Hajdas (Ed.), Game Changers in Management (pp. 117-127). Publishing House of Wroclaw University of Economics and Business.
Keywords: student experience; quality management system; quality measurement; universities; doświadczenia studenta; systemy zarządzania jakością; pomiar jakości; szkoły wyższe